2018
DOI: 10.1111/jpn.13007
|View full text |Cite
|
Sign up to set email alerts
|

Response of broiler chickens reared at high density to dietary supplementation with licorice extract and probiotic

Abstract: This study evaluated the effects of licorice extract and probiotic on performance, excreta characteristics and welfare‐related parameters of broiler chickens reared in high stocking density. Three hundred and thirty‐six 1‐day old broiler chicks (Ross 308) were used in a completely randomized design with five treatments and four replicates for 42 days. Treatments were as follows: (a) positive control (PC, 12 chicks/m2); (b) negative control (NC, 18 chicks/m2); (c) NC + 500 ppm licorice extract (LE); (d) NC + 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
2
19
2
Order By: Relevance
“…The increment in abdominal fat depot at HSD was consistent with the previous findings that HSD increased abdominal fat percent in broilers (Beg et al, 2011;Siaga et al, 2017). However, few studies found no significant effect on abdominal fat deposition of high stocking density in broilers (Tong et al 2012;Rashidi et al, 2019). These disparities might be due to the differences in the scale of SD, housing conditions, and dietary composition in these studies.…”
Section: Carcass Characteristicsmentioning
confidence: 75%
See 1 more Smart Citation
“…The increment in abdominal fat depot at HSD was consistent with the previous findings that HSD increased abdominal fat percent in broilers (Beg et al, 2011;Siaga et al, 2017). However, few studies found no significant effect on abdominal fat deposition of high stocking density in broilers (Tong et al 2012;Rashidi et al, 2019). These disparities might be due to the differences in the scale of SD, housing conditions, and dietary composition in these studies.…”
Section: Carcass Characteristicsmentioning
confidence: 75%
“…High stocking density negatively influences the skeletal development in broilers, as shown by an increase in leg deformations (Buijs et al, 2012;Sun et al, 2018). The leg deformation increases the risk of fracture during catching and transportation, which creates problems during processing (Averós & Estevez, 2018;Rashidi et al, 2019;Tahamtani et al, 2020). Several studies showed that HSD decreased shear strength of the tibia of broilers, but there is some discrepancy in the effect of HSD on the concentrations of calcium (Ca) and phosphorus (P) in tibia of broilers reared in the litter-floor system (Baitshotlhi et al, 2014;Sun et al, 2018).…”
mentioning
confidence: 99%
“…In the current study, the use of G. glabra extract powder at 0.25, 0.5, and 1 g/kg feed has improved the growth performance of broiler chickens over 35 days. Previous studies reported that dietary GE enhanced the body gain and feed efficiency in broiler chickens (31) and it has been recommended to be an alternative to infeed antibiotics growth promoters in broiler chickens (32,33). GE has a dual role in promoting growth of broiler chickens: one was to improve digestion (34) and the other may be related to its active components, mainly flavonoids, pentacyclic triterpene, and glycyrrhizin (35).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific literature has witnessed the global impact of this herb on the performance, carcass traits, and meat quality of poultry, when their diet is supplemented with licorice ( G. glabra ) either in feed and/or in drinking water [6]. In broiler chickens, probiotic and licorice extract (500 ppm) increased body weight gain of broilers exposed to high stocking density [62]. Drinking water supplementation of LE has been suggested to be an alternative to in-feed antibiotic growth promoter in broiler chickens [45].…”
Section: Beneficial Role Of Licoricementioning
confidence: 99%
“…Drinking water supplementation of LE has been suggested to be an alternative to in-feed antibiotic growth promoter in broiler chickens [45]. Body weight gain (BWG) was improved in birds reared at high stocking density by licorice extract (500 ppm) but not the feed conversion ratio (FCR) [62]. This was further improved by the addition of probiotics (200 ppm).…”
Section: Beneficial Role Of Licoricementioning
confidence: 99%